Public debt management and fiscal vulnerability: potential roles of supreme audit institution - Khan, Tanveer Akhter Hossain (BRAC University, 2010)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Governance and Development, 2009.